On the behaviour of the functional components of government expenditures during fiscal consolidations - Castro, Vítor (2016)
This paper analyses how the functional components and sub-components of government expenditures are affected by fiscal consolidations. A fixed-effects estimator is employed over a panel of 15 European Union countries during the period 1990-2012. The results show that spending on public services increases during fiscal consolidations, while spending on defence, public order, health, education and social protection is significantly cut. A more disaggregated analysis proves that fiscal consolidations are harmful for important social public expenditures, undermining citizens‟ safety, health assistance, investment in human capital and social protection. Public services are likely to be increased due to a rise in public debt transactions observed during periods of fiscal consolidation. All this evidence has proved to be stronger in a particular group of countries, known in the literature as PIIGS.